Targeting of the C-Type Lectin Receptor Langerin Using Bifunctional Mannosylated Antigens - Li, Rui-Jun Eveline; Hogervorst, Tim P.; Achilli, Silvia; Bruijns, Sven C. M.; Spiekstra, Sander; Vivès, Corinne; Thépaut, Michel; Filippov, Dmitri V.; van der Marel, Gijs A.; van Vliet, Sandra J.; Fieschi, Franck; Codée, Jeroen D. C.; et al. (Frontiers in Cell and Developmental Biology, 2020)
Langerhans cells are antigen presenting cells that reside in the skin. They uniquely express high levels of the C-type lectin receptor (CLR) Langerin (CD207), which is an attractive target for antigen delivery in immunotherapeutic vaccination strategies against cancer. We here assess a library of 20 synthetic, well-defined mannoside clusters, built up from one, two, three of six mono-, di- or trimannosides, appended to an oligopeptide backbone, for binding with Langerin using Surface Plasmon Resonance and flow cytometric quantification. It is found that Langerin binding affinity increases with increasing number of mannosides. Hexavalent presentation of the mannosides resulted in binding affinities ranging from 3 to 12 µM. Trivalent presentation of the di- and trimannosides led to Langerin affinity in the same range. The model melanoma gp100 antigenic peptide was subsequently equipped with a hexavalent cluster of the di- and trimannosides as targeting moieties. Surprisingly, although the bifunctional conjugates were taken up in Langerhans cells in a Langerin dependent manner, limited antigen presentation to cytotoxic T cells was observed. These results indicate that targeting glycan moieties on immunotherapeutic vaccines should not only be validated for target binding, but also on the continued effects on biology, such as antigen presentation to both CD8+ and CD4+ T cells.